Distributed power generation variable frequency driving cable and preparation method thereof
By using modified magnesium hydroxide and other components in the outer sheath layer material of the frequency converter cable, the problems of poor flame retardant performance and insufficient rat resistance are solved, and higher flame retardant, smoke suppression, anti-aging and rat resistance are achieved.
Patent Information
- Application Number
- CN202411766087.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The outer sheath material of existing variable frequency cables has poor flame retardant properties, is prone to combustion, and is threatened to operate safely under the invasion of pests (such as mice).
The outer sheath layer material consisting of polypropylene resin, ethylene-vinyl acetate copolymer, modified magnesium hydroxide and lubricant is used to enhance the flame retardant, smoke suppression, anti-aging and mouse-proof properties of the material through the preparation process of modified magnesium hydroxide.
It significantly improves the flame retardant, smoke suppression, anti-aging and rat-proof performance of the cable, ensuring the safe operation of the cable under high temperature and pest damage.
Smart Images

Figure BDA0005168983730000031 
Figure BDA0005168983730000041 
Figure BDA0005168983730000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of power cables, and in particular, relates to a distributed power generation variable frequency drive cable and a preparation method thereof. Background Art
[0002] Distributed generation (DG), also known as distributed generation, decentralized generation, and decentralized generation, is a technology and system that uses a variety of small, grid-connected devices to generate electricity and store energy. It is a relatively decentralized power generation method and a modular and more flexible technology. Distributed generation often uses variable frequency cables. The structure of variable frequency cables includes three main insulated wires and three neutral insulated wires. The inner sheath, copper tape, outer sheath, and outer sheath are arranged outside the main insulated wires and the neutral insulated wires in turn to form a 3+3 core structure, so that the cable has a strong voltage impact resistance, can withstand the pulse voltage during high-speed and frequent frequency conversion, and has a good protective effect on the frequency converter. However, with the development of industry and the improvement of living standards, the requirements for the performance of variable frequency cables are getting higher and higher. Since the outermost layer of the variable frequency cable is the outer sheath layer, which is directly in contact with the external environment, the outer sheath layer plays a vital role in the performance of the cable.
[0003] Common cable outer sheath materials include polypropylene, polyethylene, cross-linked polyethylene, polyvinyl chloride, etc. Among them, polypropylene is a thermoplastic synthetic resin with excellent performance, chemical resistance, heat resistance, electrical insulation, high-strength mechanical properties and good high wear resistance processing performance. It is a very high-quality outer sheath material. However, polypropylene has a low oxygen index and poor flame retardant properties. It is easy to burn when encountering open flames. Not only that, there are more rats in the south, especially in summer. According to statistics, 1 / 4 of the unexplained fires in cities are caused by rats biting off cables. It can be seen that rats and other harmful organisms bring great hidden dangers to the safe operation of electrical facilities such as wires and cables. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of power cable technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a distributed power generation variable frequency drive cable and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A distributed power generation variable frequency drive cable consists of a cable core, a filling material, a metal shielding layer, an aluminum-plastic composite layer and an outer sheath layer.
[0007] A method for preparing a distributed power generation variable frequency drive cable comprises the following steps:
[0008] An insulating layer is extruded on three main insulated core conductors, and then an insulating layer is extruded on three neutral core conductors to form a cable core, the cable core is covered with a metal shielding layer, a filler is added in the gap, and then an aluminum-plastic composite layer is wrapped on the surface of the metal shielding layer, and finally an outer sheath layer is extruded on the surface of the aluminum-plastic composite layer to obtain a distributed power generation variable frequency drive cable.
[0009] Furthermore, the cable core includes three main insulated cores and three neutral cores.
[0010] Furthermore, the main insulated core includes a main insulated core conductor and a main insulated core insulation layer.
[0011] Furthermore, the neutral core includes a neutral core conductor and a neutral core insulation layer.
[0012] Furthermore, the main insulated core conductor is a copper conductor.
[0013] Furthermore, the material of the insulation layer of the main line insulation core is polyethylene.
[0014] Furthermore, the neutral line core conductor is a copper conductor.
[0015] Furthermore, the material of the neutral line core insulation layer is polyethylene.
[0016] Furthermore, the filler is glass fiber rope.
[0017] Furthermore, the material of the metal shielding layer is copper tape.
[0018] Furthermore, the material of the outer sheath layer includes the following raw materials in parts by weight: 70-90 parts of polypropylene resin, 22-30 parts of ethylene-vinyl acetate copolymer, 15-25 parts of modified magnesium hydroxide, and 4-6 parts of lubricant.
[0019] Furthermore, the lubricant is one of paraffin and epoxidized soybean oil.
[0020] The outer sheath layer material is based on polypropylene, which gives the material excellent mechanical properties and electrical insulation properties; the added ethylene-vinyl acetate copolymer has good compatibility with the polypropylene matrix, is easy to process, and has excellent weather resistance, which can enhance the material's anti-aging properties.
[0021] Further, the modified magnesium hydroxide is prepared by the following steps:
[0022] S1. Dissolve vanillin amine hydrochloride in deionized water, add sodium hydroxide solution (mass fraction 12%), stir for 15 minutes, filter, dry at room temperature for 12 hours, add to a three-necked flask, add tetrahydrofuran and stir continuously to completely dissolve the solid, add triethylamine and acryloyl chloride, introduce nitrogen into the device as a protective gas, stir at room temperature for 4 hours, and after the reaction is completed, add dichloromethane for extraction, wash the organic phase with hydrochloric acid (mass fraction 8%) and saturated brine in turn, dry with anhydrous magnesium sulfate, evaporate with a rotary evaporator, and finally dry in vacuum to obtain intermediate 1; the ratio of vanillin amine hydrochloride, deionized water, sodium hydroxide solution, tetrahydrofuran, triethylamine, and acryloyl chloride is 15.3g:100mL:50mL:100mL:15mL:8.9g;
[0023] Vanillin amine hydrochloride is purified by sodium hydroxide solution, and the purified and dried vanillin amine hydrochloride is subjected to amidation reaction with acryloyl chloride to obtain intermediate 1. The specific reaction process is as follows:
[0024]
[0025] S2. In a three-necked flask, the intermediate 1, azobisisobutyronitrile (AIBN) and N,N-dimethylformamide (DMF) were stirred and mixed uniformly, and mercaptopropionic acid was added dropwise, and the temperature of the system was maintained at 70°C. The reaction was carried out for 6 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:1), and the eluent was removed by rotary evaporation to obtain intermediate 2; the ratio of the amount of intermediate 1, azobisisobutyronitrile, N,N-dimethylformamide, and mercaptopropionic acid was 20.7 g:0.3 g:100 mL:10.6 g;
[0026] Under the action of AIBN, the unsaturated carbon-carbon double bond on intermediate 1 undergoes a thiol-ene click reaction with the thiol group on mercaptopropionic acid to obtain intermediate 2. The specific reaction process is as follows:
[0027]
[0028] S3. At room temperature, magnesium hydroxide and ethanol aqueous solution were added to a flask, stirred at high speed for 30 min under a high shear mixing emulsifier, γ-aminopropyltriethoxysilane (silane coupling agent KH-550) was added, and the mixture was stirred at high speed for 120 min under a high shear mixing emulsifier. After the reaction was completed, the mixture was filtered and dried under vacuum to obtain pre-modified magnesium hydroxide; the ratio of magnesium hydroxide, ethanol aqueous solution and γ-aminopropyltriethoxysilane was 1 g: 100 mL: 5.7 g.
[0029] The silane coupling agent KH-550 hydrolyzes the silane alkoxy groups to generate Si-OH, which can react with the hydroxyl groups on the surface of magnesium hydroxide to introduce amino active groups to obtain pre-modified magnesium hydroxide;
[0030] S4. Add N,N-dimethylformamide and pre-modified magnesium hydroxide to a flask, disperse evenly by ultrasonication for 30 minutes, add dicyclohexylcarbodiimide (DCC, dehydrating agent) and intermediate 2, slowly heat to 60°C, start magnetic stirring (speed 1000r / min), stop heating after stirring for 8 hours, filter after the temperature in the reaction bottle drops to 30°C, wash with anhydrous ethanol 3-4 times, and freeze-dry to obtain modified magnesium hydroxide; the ratio of N,N-dimethylformamide, pre-modified magnesium hydroxide, dicyclohexylcarbodiimide, and intermediate 2 is 100mL:1g:4.6g:7.2g;
[0031] Under the action of DCC, the amino group in the pre-modified magnesium hydroxide undergoes an amidation reaction with the carboxyl group in the intermediate 2 molecule to obtain modified magnesium hydroxide;
[0032] The prepared modified magnesium hydroxide is connected to an organic molecular chain, and the organic molecular chain contains hydrophobic groups such as benzene rings and amide groups, which can enhance the surface hydrophobicity of magnesium hydroxide to a certain extent, improve the compatibility of magnesium hydroxide with a polypropylene matrix, and the magnesium hydroxide can be evenly dispersed in the matrix, reducing the agglomeration phenomenon, thereby reducing the impact on the mechanical strength of the matrix, and making the performance of magnesium hydroxide fully exerted, greatly enhancing the flame retardant and smoke suppression properties of the matrix; in addition, the organic molecular chain connected to the modified magnesium hydroxide belongs to a capsaicin derivative, containing a phenolic group, which can enhance the anti-aging properties of the matrix. Moreover, as a repellent, capsaicin can act on the peripheral nerve endings and central nerves of mice, inhibit the release of acetylcholine, hinder the conduction of synaptic nerves, have a stimulating effect on mice, and can improve the rodent-proof performance of the cable; finally, the introduced sulfur element can release strong acids such as sulfuric acid under high temperature conditions, promote the dehydration of the substrate into carbon, and can also exert excellent flame retardant properties in the condensed phase, and can synergize with magnesium hydroxide to greatly enhance the flame retardant properties of the matrix;
[0033] It should be further explained that the organic molecular chain grafted onto the inorganic filler magnesium hydroxide can effectively prevent the migration and seepage of small organic molecules and ensure the long-term stability of the modified magnesium hydroxide.
[0034] Beneficial effects of the present invention:
[0035] The cable of the present invention is composed of a cable core, a filler, a metal shielding layer, an aluminum-plastic composite layer and an outer sheath layer;
[0036] 1. The outer sheath material is based on polypropylene, which gives the cable excellent mechanical properties and electrical insulation properties;
[0037] 2. The added ethylene-vinyl acetate copolymer can enhance the anti-aging performance of the cable;
[0038] 3. By modifying magnesium hydroxide, compared with ordinary magnesium hydroxide, it has better compatibility with the polypropylene matrix, which can greatly enhance the flame retardant, smoke suppression, anti-aging and rodent-proof properties of the cable, and the performance is long-lasting and stable and not easy to fall off;
[0039] Therefore, the cable prepared by the present invention has good mechanical properties, and has stable and efficient flame retardant, smoke suppression, anti-aging and rodent-proof properties, and has important application value in the field of power cable technology. DETAILED DESCRIPTION
[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Embodiment 1
[0042] Preparation of modified magnesium hydroxide:
[0043] S1. Dissolve 15.3 g of vanillin amine hydrochloride in 100 mL of deionized water, add 50 mL of sodium hydroxide solution (mass fraction 12%), stir for 15 min, filter, dry at room temperature for 12 h, add to a three-necked flask, add 100 mL of tetrahydrofuran and stir continuously to completely dissolve the solid, then add 15 mL of triethylamine and 8.9 g of acryloyl chloride, introduce nitrogen as a protective gas into the device, stir at room temperature for 4 h, and after the reaction is complete, add dichloromethane for extraction, wash the organic phase with hydrochloric acid (mass fraction 8%) and saturated brine in turn, dry with anhydrous magnesium sulfate, evaporate with a rotary evaporator, and finally dry in vacuum to obtain intermediate 1;
[0044] S2, in a three-necked flask, 20.7g of intermediate 1, 0.3g of azobisisobutyronitrile and 100mL of N,N-dimethylformamide were stirred and mixed evenly, and then 10.6g of mercaptopropionic acid was added dropwise, and the temperature of the system was maintained at 70°C. The reaction was carried out for 6h. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:1), and the eluent was removed by rotary evaporation to obtain intermediate 2;
[0045] S3. At room temperature, add 1 g of magnesium hydroxide and 100 mL of ethanol aqueous solution into a flask, stir at high speed for 30 min under a high shear mixer, add 5.7 g of γ-aminopropyltriethoxysilane, continue stirring at high speed for 120 min under a high shear mixer, and after the reaction is complete, filter and vacuum dry to obtain pre-modified magnesium hydroxide;
[0046] S4. Add 100 mL of N,N-dimethylformamide and 1 g of pre-modified magnesium hydroxide into a flask, disperse evenly by ultrasonication for 30 min, add 4.6 g of dicyclohexylcarbodiimide and 7.2 g of intermediate 2, slowly heat to 60 °C, start magnetic stirring, stop heating after stirring for 8 h, wait for the temperature in the reaction bottle to drop to 30 °C, filter, wash 3 times with anhydrous ethanol, and freeze-dry to obtain modified magnesium hydroxide.
[0047] Embodiment 2
[0048] Preparation of modified magnesium hydroxide:
[0049] S1, 30.6g of vanillin amine hydrochloride was dissolved in 200mL of deionized water, and then 100mL of sodium hydroxide solution (mass fraction 12%) was added, and the mixture was filtered after stirring for 15min. After drying at room temperature for 12h, the mixture was added to a three-necked flask, and 200mL of tetrahydrofuran was added and stirred continuously to completely dissolve the solid. Then 30mL of triethylamine and 17.8g of acryloyl chloride were added, and nitrogen was introduced into the device as a protective gas. The mixture was stirred at room temperature for 4h. After the reaction was completed, dichloromethane was added for extraction, and the organic phase was washed with hydrochloric acid (mass fraction 8%) and saturated brine in turn, and then dried with anhydrous magnesium sulfate, evaporated with a rotary evaporator, and finally dried in vacuum to obtain intermediate 1;
[0050] S2, in a three-necked flask, 41.4 g of intermediate 1, 0.6 g of azobisisobutyronitrile and 200 mL of N,N-dimethylformamide were stirred and mixed evenly, and then 21.2 g of mercaptopropionic acid was added dropwise, and the temperature of the system was maintained at 70°C. The reaction was carried out for 6 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:1), and the eluent was removed by rotary evaporation to obtain intermediate 2;
[0051] S3. At room temperature, 2 g of magnesium hydroxide and 200 mL of ethanol aqueous solution were added to a flask, and the mixture was stirred at high speed for 30 min under a high shear mixer emulsifier. 11.4 g of γ-aminopropyltriethoxysilane was added, and the mixture was stirred at high speed for 120 min under a high shear mixer emulsifier. After the reaction was completed, the mixture was filtered and dried in vacuo to obtain pre-modified magnesium hydroxide.
[0052] S4. Add 200 mL of N,N-dimethylformamide and 2 g of pre-modified magnesium hydroxide into a flask, disperse evenly by ultrasonication for 30 min, add 9.2 g of dicyclohexylcarbodiimide and 14.4 g of intermediate 2, slowly heat to 60 °C, start magnetic stirring, stop heating after stirring for 8 h, wait for the temperature in the reaction bottle to drop to 30 °C, filter, wash 3 times with anhydrous ethanol, and freeze-dry to obtain modified magnesium hydroxide.
[0053] Embodiment 3
[0054] 70 g of polypropylene resin and 22 g of ethylene-vinyl acetate copolymer were placed in an oven and dried for 12 h. The dried polypropylene resin, ethylene-vinyl acetate copolymer, 15 g of modified magnesium hydroxide prepared in Example 1, and 4 g of paraffin were added to a high-speed mixer and stirred for 30 min. The mixture was added to a twin-screw extruder, melt-blended, and extruded to obtain an outer sheath layer material.
[0055] Embodiment 4
[0056] 80g of polypropylene resin and 26g of ethylene-vinyl acetate copolymer were placed in an oven and dried for 12h. The dried polypropylene resin, ethylene-vinyl acetate copolymer, 20g of modified magnesium hydroxide prepared in Example 2 and 5g of epoxidized soybean oil were added to a high-speed mixer and stirred for 30min. The mixture was added to a twin-screw extruder, melt-blended and extruded to obtain an outer sheath layer material.
[0057] Embodiment 5
[0058] 90 g of polypropylene resin and 30 g of ethylene-vinyl acetate copolymer were placed in an oven and dried for 12 h. The dried polypropylene resin, ethylene-vinyl acetate copolymer, 25 g of modified magnesium hydroxide obtained in Example 2, and 6 g of epoxidized soybean oil were added to a high-speed mixer and stirred for 30 min. The mixture was added to a twin-screw extruder, melt-blended, and extruded to obtain an outer sheath layer material.
[0059] Embodiment 6
[0060] A polyethylene insulation layer is extruded on three copper conductors to obtain a main insulated core, and then a polyethylene insulation layer is extruded on three copper conductors to obtain a neutral core. The main insulated cores are arranged in a triangle, and then the neutral core is arranged in an inverted triangle to form a cable core. The cable core is coated with a copper tape to form a metal shielding layer, a glass fiber rope is added into the gap as a filler, and then an aluminum-plastic composite layer is wrapped on the surface of the metal shielding layer; finally, 90g of polypropylene resin and 30g of ethylene-vinyl acetate copolymer are placed in an oven and dried for 12h, and the dried polypropylene resin, ethylene-vinyl acetate copolymer, 25g of modified magnesium hydroxide prepared in Example 2, and 6g of epoxy soybean oil are added to a high-speed mixer, stirred for 30min, added to a twin-screw extruder, melt blended, and coated on the aluminum-plastic composite layer through an extruder to obtain a distributed power generation variable frequency drive cable.
[0061] Comparative Example 1
[0062] Ordinary magnesium hydroxide of the same mass was used to replace the modified magnesium hydroxide in Example 5, and the remaining steps were the same as those in Example 5 to obtain the outer sheath layer material.
[0063] Comparative Example 2
[0064] The modified magnesium hydroxide in Example 5 was replaced by a commercially available aminosulfonic acid flame retardant of equal mass, and the remaining steps were the same as those in Example 5 to obtain an outer sheath layer material.
[0065] Comparative Example 3
[0066] Use commercially available rat and ant-proof cables.
[0067] Embodiments 3, 4, 5, and comparative examples 1 and 2 were made into corresponding shapes to be tested according to different test standards, and the following performance tests were performed:
[0068] The tensile properties are determined using the national standard GB / T 1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics";
[0069] The oxidation induction time was determined using the national standard GB / T 19466.6-2009 "Plastic Differential Scanning Calorimetry";
[0070] The smoke density is measured using the national standard GB / T 8323.2-2008 "Plastic smoke generation Part 2: Single chamber method for determination of smoke density test method";
[0071] The national standard GB / T 2406-2008 "Test method for combustion performance of plastics" is used to measure the limiting oxygen index of the sample after standing at room temperature for 200 days;
[0072] The measured results are shown in Table 1:
[0073] Table 1
[0074]
[0075] The protection level of rats in Example 6 and Comparative Example 2 was determined using the standard JB / T 10696.10-2011 "Test methods for mechanical and physical and chemical properties of wires and cables Part 10: Rat gnawing test";
[0076] The measured results are shown in Table 2:
[0077] Table 2
[0078] Test items Embodiment 6 Comparative Example 3 Rat protection level Significant better
[0079] It can be seen from Table 1 that the flame retardant, smoke suppression and aging resistance of the outer sheath layer materials prepared in Examples 3, 4 and 5 of the present invention are higher than those of the comparative example, and the performance is long-lasting and stable; with the increase of the content of modified magnesium hydroxide, the performance of the outer sheath layer material is more excellent, and the influence on the mechanical properties is smaller; it can be seen from Table 2 that the cable prepared in Example 6 of the present invention has better rodent-proof performance than the comparative example 3. Therefore, the present invention has important application value in the field of power cable technology.
[0080] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0081] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A distributed power generation variable frequency drive cable, consisting of a cable core, a filler, a metal shielding layer, an aluminum-plastic composite layer and an outer sheath layer, characterized in that: The material of the outer sheath layer includes the following raw materials in parts by weight: 70-90 parts of polypropylene resin, 22-30 parts of ethylene-vinyl acetate copolymer, 15-25 parts of modified magnesium hydroxide, and 4-6 parts of lubricant.
2. A distributed power generation variable frequency drive cable according to claim 1, characterized in that: The modified magnesium hydroxide is prepared by the following steps: S1, dissolve vanillin amine hydrochloride in deionized water, add sodium hydroxide solution, stir for 15 minutes, filter, dry at room temperature for 12 hours, add to a three-necked flask, add tetrahydrofuran and stir continuously to completely dissolve the solid, then add triethylamine and acryloyl chloride, introduce nitrogen into the device, stir at room temperature for 4 hours, and after the reaction is completed, extract, wash, dry, rotary evaporate, and finally vacuum dry to obtain intermediate 1; S2, the intermediate 1, azobisisobutyronitrile and N,N-dimethylformamide were stirred and mixed evenly, and mercaptopropionic acid was added dropwise, and the mixture was reacted at 70° C. for 6 h. After the reaction was completed, the mixture was rotary evaporated, purified by column chromatography, and rotary evaporated to obtain the intermediate 2; S3. At room temperature, magnesium hydroxide and ethanol aqueous solution were added to a flask, and the mixture was stirred at high speed for 30 min under a high shear mixer emulsifier, and γ-aminopropyltriethoxysilane was added, and the mixture was stirred at high speed for 120 min under a high shear mixer emulsifier. After the reaction was completed, the mixture was filtered and dried in vacuo to obtain pre-modified magnesium hydroxide; S4. Add N,N-dimethylformamide and pre-modified magnesium hydroxide into a flask, disperse them evenly by ultrasonication for 30 minutes, add dicyclohexylcarbodiimide and intermediate 2, slowly heat up to 60°C, start magnetic stirring, stop heating after stirring for 8 hours, wait until the temperature in the reaction bottle drops to 30°C, filter, wash, and freeze-dry to obtain modified magnesium hydroxide.
3. A distributed power generation variable frequency drive cable according to claim 2, characterized in that: In step S1, the ratio of vanillin amine hydrochloride, deionized water, sodium hydroxide solution, tetrahydrofuran, triethylamine and acryloyl chloride is 15.3 g: 100 mL: 50 mL: 100 mL: 15 mL: 8.9 g.
4. A distributed power generation variable frequency drive cable according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, azobisisobutyronitrile, N,N-dimethylformamide, and mercaptopropionic acid is 20.7 g:0.3 g:100 mL:10.6 g.
5. A distributed power generation variable frequency drive cable according to claim 2, characterized in that: In step S3, the ratio of magnesium hydroxide, ethanol aqueous solution, and γ-aminopropyltriethoxysilane is 1 g:100 mL:5.7 g.
6. A distributed power generation variable frequency drive cable according to claim 2, characterized in that: In step S4, the ratio of the amount of N,N-dimethylformamide, pre-modified magnesium hydroxide, dicyclohexylcarbodiimide, and intermediate 2 is 100 mL: 1 g: 4.6 g: 7.2 g.
7. A distributed power generation variable frequency drive cable according to claim 1, characterized in that: The lubricant is one of paraffin and epoxidized soybean oil.
8. The method for preparing a distributed power generation variable frequency drive cable according to claim 1, characterized in that: The following steps are involved: An insulating layer is extruded on three main insulated core conductors, and then an insulating layer is extruded on three neutral core conductors to form a cable core, the cable core is covered with a metal shielding layer, a filler is added in the gap, and then an aluminum-plastic composite layer is wrapped on the surface of the metal shielding layer, and finally an outer sheath layer is extruded on the surface of the aluminum-plastic composite layer to obtain a distributed power generation variable frequency drive cable.
Citation Information
Patent Citations
Crosslinked polyethylene insulated flame-retardant polyvinyl chloride sheath variable frequency cable
CN114864165A
Preparation process of anti-rat and anti-termite flame-retardant power cable for urban rail transit
CN116622144A
Rat-bite-proof polypropylene composite material and preparation method thereof
CN117801422A
Oil-resistant B1-grade electron beam irradiation crosslinking low-smoke halogen-free flame-retardant polyolefin sheath material
CN118185169A
Complex cable for pneumatic actuator and method of forming the same
KR1020170012673A
Cited By
Flame-retardant cable and preparation method thereof
CN121554873A
Flame-retardant cable and method for producing the same
CN121554873B